The Effecs of Servant Leadership, Organizational Climate, and Work Motivation on Teacher’s Performance in A Level Education Centre - Linda Liana; Dylmoon Hidayat (Kelola: Jurnal Manajemen Pendidikan, 2021)
Teachers are the front-liners that determine the quality of education given. Therefore, teacher’s performance must be studied to make sure that the quality of education has reached the standard set before. There are many factors that affect teacher’s performance such as, the leadership style, organizational climate and work motivation. This research is conducted to find out if there is a positive effect of servant leadership, organizational climate and work motivation on teacher’s performance in A Level Education Centre. This is a quantitative research with 36 respondents. Descriptive statistic, path analysis and multiple linear regression were used in analyzing the collected data. The outcome showed that (1) servant leadership has a positive effect on teacher’s performance; (2) organizational climate has a positive effect on teacher’s performance; (3) work motivation has a positive effect on teacher’s performance. Teacher’s performance variable can be explained by servant leadership variable, organizational climate variable and work motivation variable by 62%. The rest of 38% is being explained by other variables that are not included in this research.